The Suicidal Intrusions Attributes Scale (SINAS): a new tool measuring suicidal intrusions - van Bentum, Jaël S.; Kerkhof, Ad J. F. M.; Huibers, Marcus J. H.; Holmes, Emily A.; de Geus, Stephan; Sijbrandij, Marit (Frontiers in Psychiatry, 2023)
Introduction: suicidal intrusions are uncontrollable, intrusive mental images (e.g., visualizing a future suicidal act). They may also be called suicidal 'flash-forwards'. Despite the importance of integrating the assessment of suicidal intrusions into clinical routine-assessment, quick self-report screening instruments are lacking. This study describes the development of a new instrument (Suicidal Intrusions Attributes Scale; SINAS) to assess the severity and characteristics of suicidal intrusions and examines its psychometric properties. Method: the sample included currently suicidal outpatient with elevated levels of depression recruited across mental health institutions in the Netherlands (N=168). Instruments administered were 10-item SINAS, the Suicidal Ideation Attributes Scale (SIDAS), the Prospective Imagery Task (PIT), 4 items of the Suicidal Cognitions Interview (SCI), and the Beck Depression Inventory (BDI-II). Results: an exploratory factor analysis identified a onefactor structure. The resulting SINAS demonstrated good internal consistency (Cronbach's =.91) and convergent validity, as expected. Discussion: overall, this study demonstrated acceptable levels of accumulated initial evidence to support further research into the reliability and validity of the measure in a depressed clinical population with suicidal ideation. The SINAS may be a useful screening tool for suicidal intrusions in both research and clinical settings.